Terra is a left–right asymmetry gene required for left–right synchronization of the segmentation clock - Saúde, Leonor (2005)
To establish the vertebrate body plan, it is fundamental to create left–right asymmetry in the lateral-plate mesoderm to correctly position the organs. However, it is also crucial to maintain symmetry between the left and the right sides of the presomitic mesoderm, ensuring the allocation of symmetrical body structures, such as the axial skeleton and skeletal muscles. Here, we show that terra is an early left-sided expressed gene that links left–right patterning with bilateral synchronization of the segmentation clock.